Odpowiedzi

Najlepsza Odpowiedź!
2010-02-12T21:51:20+01:00
A)
x+3y=3
x-y =5

x=3-3y
3-3y-y=5
-4y=2
y=-2

x=3-3*(-2)
x=3+6
x=9


b)
2x-y=10
x+5y=-17

x=-17-5y
2(-17-5y)-y=10
-34-10y-y=10
-11y=44
y=-4

x=-17-5*(-4)
x=-17+20
x=3


c)
3m+n=9
2m-5n=-11

n=9-3m
2m-5(9-3m)=-11
2m-45+15m=-11
17m=34
m=2

n=9-3*2
n=9-6
n=3


d)
4a-2=b
3a+7b=1,5

-b=-4a+2
b=4a-2
3a+7(4a-2)=1,5
3a+28a-14=1,5
31a=15,5
a=0,5

b=4*0,5-2
b=2-2
b=0


e)
5x=4-2y
4x=y -3

-y=-3-4x
y=3+4x
5x=4-2(3+4x)
5x=4-6-8x
13x=-2
x=-2/13

y=3+4*(-2/13)
y=3-8/13
y=31/13



f)
6x-3y=9
x+5y=-9,5

x=-9,5-5y
6(-9,5-5y)-3y=9
-57-30y-3y=9
-33y=66
y=-2

x=-9,5-5*(-2)
x=-9,5+10
x=0,5
3 3 3
2010-02-13T00:44:35+01:00
X+3y=3
x-y =5

1.)
x=3-3y
3-3y-y=5

-4y=2
y=-0,5

x=3-3*(-0,5)
x=3+1,5
x=4,5

x=4,5
y=-0,5

2.)
2x-y=10
x+5y=-17

2x-y=10
x=-17-5y

2(-17-5y)-y=10
x=-17-5y

-34-10y-y=10
-11y=44
y=-4

x=-17-5*(-4)
x=-17+20
x=3

x=3
y=-4

3.)
3m+n=9
2m-5n=-11

n=9-3m
2m-5(9-3m)=-11

2m-45+15m=-11
17m=34
m=2

n=9-3*2
n=9-6
n=3

m=2
n=3

4.)
4a-2=b
3a+7b=1,5

4a-2=b
3a+7(4a-2)=1,5

3a+28a-14=1,5
31a=15,5
a=2

b=4*2-2
b=6

a=2
b=6

5.)
nie wiem, gdzie jest " = " w drugim równaniu

5x=4-2y
4x+y -3

6.)
6x-3y=9
x+5y=-9,5

6x-3y=9
x=-9,5-5y

6(-9,5-5y)-3y=9
-57-30y-3y=9
-33y=66
y=-2

x=-9,5-5*(-2)
x=-9,5+10
x=0,5

x=0,5
y=-2
2 1 2